IMPLEMENTASI PROGRAM KESEJAHTERAAN SOSIAL ANAK DI DINAS SOSIAL PROVINSI KALIMANTAN TIMUR - Saprudin Saida Panda; Djumadi .; Fajar Apriani (Jurnal Administrative Reform, 2017)
The purpose of this study was to describe and analyze the implementation of the Child Welfare Program in Samarinda by the Social Service of East Kalimantan Province and determine the factors that support and hinder the implementation of the program. This research was a qualitative research, with research sites in East Kalimantan Provincial Social Service and several other research sites. Primary data obtained from interviews with selected informants, as well as from direct observation in the study area. While secondary data were collected from data held by the agency.